Untouchability in Rural India - Shah,Ghanshyam; Harsh Mander, Sukhadeo Thorat, Satish Deshpande,Amita Baviskar (Jaipur: Rawat Publications, 2023)
This book is a focused and systematic documentation of the incidence and extent of the practice of untouchability in India.